2011
DOI: 10.1007/s00066-011-2221-y
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability of clinical target volume delineation in supra-diaphragmatic Hodgkin’s disease

Abstract: This significant variability confirms the need to apply specific guidelines to improve contouring uniformity in Hodgkin's lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Inter-observer studies are necessary in order to quantify delineation uncertainties within an institutional contouring protocol or clinical trial, to validate delineation guidelines, and to evaluate automatic segmentation tools or new image modalities for analysis of tumor behavior [1,6,8,9,35,46].…”
Section: Critical Discussion Of Evaluation Parameters For Inter-obsermentioning
confidence: 99%
“…Inter-observer studies are necessary in order to quantify delineation uncertainties within an institutional contouring protocol or clinical trial, to validate delineation guidelines, and to evaluate automatic segmentation tools or new image modalities for analysis of tumor behavior [1,6,8,9,35,46].…”
Section: Critical Discussion Of Evaluation Parameters For Inter-obsermentioning
confidence: 99%
“…A variety of methods have been proposed to quantify interobserver variability in radiotherapy contouring, especially in target definition [18]. Some studies evaluated the variability in target volume delineation using descriptive statistics and parameters describing the distribution of volumes and diameters, such as mean, standard deviation, range, and dispersion of the distribution, such as COV [21][22][23][24][25][26][27][28]. The majority of studies deal with approaches that describe the overlapping area between contoured volumes, using metrics, such as CI and DC [22][23][24][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of specific studies focused on the agreement among radiation oncologists and therapists in EPI-based set-up quality evaluation, in several departments this task is entrusted to trained radiation therapists [14,20,21]. Interrater variability is a well-known issue in radiation therapy that affect both the treatment planning and the patient setup verification phases [1]. Wide variability in set-up quality reviews performed by physicians has been reported and related to observer's training and experience [5,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Electronic portal imaging (EPI) represents a gold standard for patient set-up verification in breast cancer radiotherapy [1,2]. It has also gained increasingly importance for intensity modulated radiotherapy (IMRT) dose verification, both pretreatment and in vivo [3], as well as for motion tracking (EPI acquired in cine mode) [4].…”
mentioning
confidence: 99%